Physical activity levels of children with visual impairments during an adapted sports camp. (May 2017) - Tindall, Daniel W; Foley, John T; Beets, Micheal W; Lieberman, Lauren J
The purpose of this study was to identify the physical activity (PA) levels of children and young people with visual impairments (VI) as they participated in closed and open skilled sports as part of a specially designed 1-week sports camp. Participants ( N  = 18; girls = 6; boys = 12; M age  = 13 years, 4 months) aged 9–19 years possessed various levels of VI. Data were collected using Actigraph GM1 accelerometers and analysed using a one-way analysis of variance (ANOVA). Findings suggest there was a significant effect of activity type on both intensity F (1.7, 28.94) = 9.86, p  = .001, η p 2 = . 37 and time spent in moderate-to-vigorous physical activity (MVPA) F (4, 68) = 6.03, p  < .001, η p 2 = . 26 . The findings of this study support the continued implementation of both closed and open skill-oriented disability sports as a means to reaching recommended MVPA levels for children and young people with VI.